Strengthening Islamic Financial Inclusion Through Sharia Fintech: Implications for MSME Development in Parepare City, Indonesia - Muzdalifah Muhammadun; Syahriyah Semaun; Andi Bahri S.; Andi Ayu Frihatni; Syamsul Ma'arif (Universitas Muhammadiyah Makassar, 2026)
The rapid growth of Sharia financial technology (fintech) has created significant opportunities to enhance Islamic financial inclusion and support the development of micro, small, and medium enterprises (MSMEs). However, empirical evidence regarding the mechanisms through which Sharia fintech influences MSME development remains limited, particularly in regional contexts in Indonesia. This study examines the mediating role of Islamic financial inclusion in the relationship between Sharia fintech services and MSME development. Using a quantitative approach, data were collected from 100 MSME owners in Parepare City, South Sulawesi, Indonesia, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Sharia fintech has a positive and significant effect on Islamic financial inclusion and MSME development. Islamic financial inclusion also positively influences MSME development. Furthermore, Islamic financial inclusion partially mediates the relationship between Sharia fintech and MSME development, suggesting that the benefits of fintech adoption are strengthened through broader access to Sharia-compliant financial services. The structural model explains 50.1% of the variance in MSME development. These findings underscore the strategic role of Sharia fintech in fostering an inclusive Islamic financial ecosystem and promoting sustainable MSME growth. While the findings provide valuable insights into Islamic digital finance, they are based on MSMEs operating in Parepare City and should therefore be interpreted within this local context. This study contributes to the literature on Islamic digital finance by providing empirical evidence on the mediating role of Islamic financial inclusion and offers practical implications for policymakers, Islamic financial institutions, and fintech providers.